SMEs, the engine of local entrepreneurship, in the framework of New Basel Capital Accord: Perspectives-opportunities and obstacles for their reinforcement by the Banking System - Chryssanthi Balomenou (European Regional Science Association (ERSA), 2004)
In the first part of my paper I will analyze the important role of SMEs as the most crucial factor for the development of the local entrepreneurship. In addition I will quote the arising difficulties in SMEs' access to loans. This part will be concluded by the presentation of the Third Consultative Paper of The Basel II Capital Accord, in relation to its impact on SMEs, focussing on the comments of the European Central Bank, World Bank Eurochabres, and of the European Private Equity and Venture Capital Association and more specifically, on those referring to SMEs.. The second part will refer to the Structure of the New Accord Three Pillars, focussing on the Basel II Capital Adequacy framework and specifically on the first pillar (Minimum Capital Requirement). Obviously, the said part will be completed by the consequences of the aforementioned topic for the SMEs. In the third and last part of my paper I will work out a critical analysis of the New Basel Capital Accord, concentrating on its pros and corns for SMEs' banking finance. Finally, my paper will contain an appendix of tables and graphs and of course the relevant references.
Keywords: 330